Effective utilization of Salvinia molesta D. Mitch. for the production of cellulase enzyme by using Aspergillus species and reuse of fungal biomass for dye degradation - Chithra, K N; Sruthy, C R; Thomas, Binu (Research in Biotechnology, 2013)
The present study reveals Salvinia molesta D. Mitch.in various concentration is used as carbon source for the production of cellulase enzyme using Aspergillus species by submerged fermentation. The basal medium supplemented with Salvinia molesta blend in the proportion of 1:0.5 as carbon source showed maximum cellulase production after 6 days of incubation at room temperature with agitation speed of 150 rpm in rotary shaker, were liberated 3.2mg/ml glucose. Methylene blue dye was completely decolourized within 6 days of incubation at room temperature with agitation speed of 150 rpm. This demonstrates the reuse of fungal biomass for dye degradation after enzyme production.